The RhoGAP crossveinless-c Interacts with Dystrophin and Is Required for Synaptic Homeostasis at the Drosophila Neuromuscular Junction. - Pilgram, G.S.; Potikanond, S.; van der Plas, M.C.; Fradkin, L.G.; Noordermeer, J.N. (Journal of Neuroscience, 2011)
Duchenne muscular dystrophy is caused by mutations in the Dystrophin gene and is characterized by muscle degeneration and the occurrence of mental deficits in a significant number of patients. Although Dystrophin and its closely related ortholog Utrophin are present at a variety of synapses, little is known about their roles in the nervous system. Previously, we reported that absence of postsynaptic Dystrophin from the Drosophila neuromuscular junction (NMJ) disrupts synaptic homeostasis, resulting in increased stimulus-evoked neurotransmitter release. Here, we show that RhoGAP crossveinless-c (cv-c), a negative regulator of Rho GTPase signaling pathways, genetically interacts with Dystrophin. Electrophysiological characterization of the cv-c-deficient NMJ and the use of presynaptic- and postsynaptic-specific transgenic rescue versus RNA interference reveal that the absence of postsynaptic cv-c results in elevated evoked neurotransmitter release. The cv-c mutant NMJ exhibits an increased number of presynaptic neurotransmitter release sites and higher probability of vesicle release without apparent changes in postsynaptic glutamate receptor numbers or function. Moreover, we find that decreasing expression of the Rho GTPase Cdc42 suppresses the high neurotransmitter release in the cv-c and Dystrophin mutants, suggesting that Cdc42 is a substrate of Cv-c. These results indicate that Dystrophin and the Rho GTPase signaling pathway likely interact at the postsynaptic side of the NMJ to maintain synaptic homeostasis. The absence of this postsynaptic pathway results in presynaptic structural and functional alterations, suggesting that retrograde signaling mechanisms are affected.